The politicisation of the climate emergency: the case of the 2019 United Kingdom general election - Alma-Pierre BONNET (E-REA)
It was fair to assume that the 2019 United Kingdom (UK) general election would be all about Brexit. The reality is actually more complex and other issues came into play in the run-up to 12 December ballot, in particular the question of environmental emergency. Several key elements can be used to explain why the environment topped the voters’ main concerns, slightly behind Brexit and health, but on a par with crime and the economy: recent natural catastrophes such as the summer heatwaves or the floods in the North of the country and the growing climate awareness among younger citizens. Chris Stark, chief executive of the Committee on Climate Change, even claimed that “this election really is the climate election” (Shukman).When one takes the general political mood into consideration, it seems quite legitimate to question this assertion and to wonder how much of an impact the environmental emergency really had during the campaign. This is what this paper will examine. Through an analysis of the media coverage and the official literature from the different political parties, we will try to define the role and the importance of the climate emergency during the 2019 campaign.